The additional benefit of residual spraying and insecticide-treated curtains for dengue control over current best practice in Cuba: Evaluation of disease incidence in a cluster randomized trial in a low burden setting with intensive routine control - Toledo, Maria Eugenia (PLoS Negl Trop Dis, 2017)
BACKGROUND: Aedes control interventions are considered the cornerstone of dengue control programmes, but there is scarce evidence on their effect on disease. We set-up a cluster randomized controlled trial in Santiago de Cuba to evaluate the entomological and epidemiological effectiveness of periodical intra- and peri-domiciliary residual insecticide (deltamethrin) treatment (RIT) and long lasting insecticide treated curtains (ITC). METHODOLOGY/PRINCIPAL FINDINGS: Sixty three clusters (around 250 households each) were randomly allocated to two intervention (RIT and ITC) and one control arm. Routine Aedes control activities (entomological surveillance, source reduction, selective adulticiding, health education) were applied in the whole study area. The outcome measures were clinical dengue case incidence and immature Aedes infestation. Effectiveness of tools was evaluated using a generalized linear regression model with a negative binomial link function. Despite significant reduction in Aedes indices (Rate Ratio (RR) 0.54 (95%CI 0.32–0.89) in the first month after RIT, the effect faded out over time and dengue incidence was not reduced. Overall, in this setting there was no protective effect of RIT or ITC over routine in the 17months intervention period, with for house index RR of 1.16 (95%CI 0.96–1.40) and 1.25 (95%CI 1.03–1.50) and for dengue incidence RR of 1.43 (95%CI 1.08–1.90) and 0.96 (95%CI 0.72–1.28) respectively. The monthly dengue incidence rate (IR) at cluster level was best explained by epidemic periods (Incidence Rate Ratio (IRR) 5.50 (95%CI 4.14–7.31)), the IR in bordering houseblocks (IRR 1.03 (95%CI 1.02–1.04)) and the IR pre-intervention (IRR 1.02 (95%CI 1.00–1.04)). CONCLUSIONS: Adding RIT to an intensive routine Aedes control programme has a transient effect on the already moderate low entomological infestation levels, while ITC did not have any effect. For both interventions, we didn’t evidence impact on disease incidence. Further studies are needed to evaluate impact in settings with high Aedes infestation and arbovirus case load.